2002
DOI: 10.1212/01.wnl.0000031421.50369.e7
|View full text |Cite
|
Sign up to set email alerts
|

Amount and type of alcohol and risk of dementia

Abstract: Monthly and weekly intake of wine is associated with a lower risk of dementia. The results do not indicate that people should start drinking or increase wine consumption to avoid dementia, but instead suggest that certain substances in wine may reduce the occurrence of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
164
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(174 citation statements)
references
References 33 publications
8
164
2
Order By: Relevance
“…Moderate wine consumption rather than alcohol consumption per se has been specifically associated with a lower risk of developing dementia and specifically Alzheimer's disease in studies over the past two decades [38,54,[72][73][74][77][78][79][80][81][82][83][84]. Wine consumption of up to approximately 75 mL per day improved cognition in 883 elderly subjects recruited from the Norwegian Hordaland Health Study [154].…”
Section: Relationship Of Wine To Cognitive Function and Dementiasmentioning
confidence: 99%
“…Moderate wine consumption rather than alcohol consumption per se has been specifically associated with a lower risk of developing dementia and specifically Alzheimer's disease in studies over the past two decades [38,54,[72][73][74][77][78][79][80][81][82][83][84]. Wine consumption of up to approximately 75 mL per day improved cognition in 883 elderly subjects recruited from the Norwegian Hordaland Health Study [154].…”
Section: Relationship Of Wine To Cognitive Function and Dementiasmentioning
confidence: 99%
“…Resveratrol reduces infection-related neuroinflammation and attenuates working memory deficits in aged mice, suggesting that resveratrol may be useful for mitigating acute cognitive disorders in elderly individuals with an infection (90). Furthermore, although moderate red wine intake has been associated with reduced incidence of Alzheimer's disease and other forms of dementia (91)(92)(93), clear evidence regarding resveratrol's role is still lacking (94,95). Thus, although resveratrol may not be able to extend overall life span in healthy individuals, it will be important to assess the degree to which it might be able to increase quality of life among the overweight and the elderly individuals by mitigating some of the negative effects of an unhealthy lifestyle.…”
Section: Sirtuin Activatorsmentioning
confidence: 99%
“…A number of dietary factors such as saturated fatty acids, higher calorie intake, and excessive alcohol (7) have been reported to increase the risk of dementia and AD (8). In particular, a number of studies have shown the close association of alcoholic consumption and dementia, although the exact mechanisms are still not known (9)(10)(11)(12)(13). Studies have been shown that frequent alcohol uptake by rats can cause mitochondrial dysfunction in neurons, leading to neurodegeneration (14).…”
Section: Introductionmentioning
confidence: 99%